Comparative Study of Post-disaster Reconstruction Paradigm and Iranian Experts’ Perspective of Reconstruction - Andalib, Alireza; Majd, Fereshteh Navidi (Journal of History Culture and Art Research, 2017)
Numerous natural disasters happen in the world annually and damages resulting from disasters and their consequences on development achievements are increasing in human communities. Hence, Post-disaster reconstruction has been developed in all aspects during the last years. The present article classifies the views of experts on post-disaster reconstruction and compares this reconstruction paradigm with the reconstruction process in Iran. This research has been conducted in the theoretical principles section of post-disaster reconstruction and is done in four steps: studying the views in post-disaster reconstruction field within a thirty-years period since 1982 to 2012; analyzing the views of the post-disaster reconstruction experts; deriving post-disaster reconstruction paradigm’s components using Grounded Theory method; and comparative study of post-disaster reconstruction paradigm and Iranian expert’s perspective of reconstruction by in-depth interviews with 10 Iranian expert who were involved in reconstruction in Iran during that period. The first part results include paradigms: Encouraging people for participation, individuals and groups participation, Procedural planning and Proactive management. Comparing these with Iranian’s experiences, shows that a systematic reconstruction plan should be based on recognition of local characteristics of region and the needs of the affected population besides the other results.